1999
DOI: 10.1016/s0378-1097(99)00456-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced pH causes structural changes in the potent mitogenic toxin of Pasteurella multocida

Abstract: Pasteurella multocida toxin is a potent mitogen that is believed to act intracellularly. On transverse urea gradient gels at pH 8.0 the toxin displayed one major unfolding transition at 4 M urea. However, at pH 6.1 the unfolding transition took place at 3.5 M urea. Circular dichroism spectra also indicated that a structural change took place at acidic pH. In addition it was found that the toxin that had been denatured in 8 M urea refolded in solution with a high recovery of biological activity. These findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…CNF1 and PMT share 24% homology in the first 500 amino acids of their respective N termini and show the highest degree of similarity in regions that are proposed to encompass transmembrane domains in both toxin molecules (amino acids 199 to 420 of CNF1 and amino acids 245 to 467 of PMT) (14,36,40,41). Despite this protein homology, recent work has indicated that the intracellular activity of PMT lies within the N terminus of the toxin.…”
Section: Discussionmentioning
confidence: 99%
“…CNF1 and PMT share 24% homology in the first 500 amino acids of their respective N termini and show the highest degree of similarity in regions that are proposed to encompass transmembrane domains in both toxin molecules (amino acids 199 to 420 of CNF1 and amino acids 245 to 467 of PMT) (14,36,40,41). Despite this protein homology, recent work has indicated that the intracellular activity of PMT lies within the N terminus of the toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Pasteurella multocida toxin is an intracellularly acting toxin Smyth et al ., 1995;1999). It is thought to bind to a ganglioside cell-surface receptor, and enter cells by endocytosis (Pettit et al ., 1993), in order to modify its target.…”
Section: Introductionmentioning
confidence: 99%
“…Its action is also inhibited by neutralizing antibody or methylamine added early but not late after toxin. PMT undergoes a conformational change at low pH, which affects its protease sensitivity and circular dichroism spectra (46,47). This suggests that PMT may be trafficked and perhaps processed through a low-pH compartment.…”
mentioning
confidence: 99%